Local Economic Potential Changes in Sei Mangkei in Simalungun District, North Sumatra - Sarosa, Chaviannisa Sagitha (MediaTrend, 2024)
This study aims to evaluate economic growth in the Sei Mangkei Special Economic Zone (SEZ) in Simalungun Regency, Indonesia. The approach used is qualitative with a descriptive method to understand the impact of SEZ on local economic development. The research collected secondary data from various sources such as reports, journals, and relevant scientific literature. The results show that the Sei Mangkei SEZ has a significant but relatively small impact on increasing the Gross Regional Domestic Product (GRDP) of Simalungun Regency. Although Sei Mangkei SEZ has succeeded in attracting investment and creating jobs, its impact on the local economy is still not in line with community expectations. Simalungun's economic growth in 2023 reached 5.07 percent, driven by the transportation and warehousing sector and exports of goods and services. However, challenges such as dependence on the central government, lack of promotion, and suboptimal infrastructure integration still need to be addressed. Policy recommendations include infrastructure improvement, promotion optimization, institutional strengthening, human resource development, and sustainable environmental management. This research is limited to the time of data collection and analysis to 2023, so recent developments may not be included. This research focuses on the Sei Mangkei SEZ in Simalungun Regency, so the results may not be generally applicable to other SEZs in Indonesia due to differences in geographical, economic, and social conditions